Zadovoljstvo študentov zdravstvene nege s problemskim učenjem - Gönc, Vida (Obzornik zdravstvene nege, 2015)
Introduction: Problem-based learning represents an educational paradigm shift from traditional to student-oriented teaching and learning philosophy. It encourages the development of independent learning and gaining of knowledge and skills needed to perform competent nursing care. The purpose of the research was to determine the satisfaction levels of full-time and parttime nursing students with the method of problem-based learning. Methods: The study employed methods of quantitative non-experimental research and a survey data collection. A total of 169 nursing students participated in the study. The data were processed by a descriptive statistics, t-test and correlation analysis. The statistical significance was tested on a 5 % risk level. Results: Average ratings of all statements regarding the students' satisfaction levels with problembased learning were very high (> 4 out of 5). According to the results, there is no statistically significant difference in satisfaction with problem-based learning between full-time and part-time students (t = -0.818, p = 0.414) and between male and female students (t = -0.002, p = 0.998). A positive impact of work experience on the satisfaction with problem-based learning was observed in part-time students employed in the health care sector. There is also a correlation between the student's age and satisfaction with problem-based learning (r = 0.198, p = 0.006). Discussion and conclusion: Research findings indicate that problem-based learning improves work motivation and encourages independent study as well as teamwork. Further research would need to investigate the problem-based learning in clinical practice and the application of theoretical knowledge in clinical environment.
Keywords: evaluation; evalvacija; learning; nursing; problem-based learning; problemsko zasnovan študij; teaching; učenje; zdravstvena nega